The Blind Spot: International Mining in Angoche and Larde, Mozambique - Sergio Chichava; Shubo Li; Michael G. Sambo (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2019)
Comparing Chinese and Irish companies in their respective dealings with local civil societies and communities, Chichava, Li, and Sambo probe the social impacts of heavy sand mining by international companies in Mozambique. They set to find out how international mining affects local social organization in terms of work, labor relations, and livelihoods, and how disputes are negotiated between the mining companies, municipal and provincial governments, and civil society groups representing the interests of local communities. Disagreements around compensation, resource depletion, and labor-relations are the primary source of controversy and tension generated by the mining projects.
Keywords: 330